Hand Robotics Rehabilitation: Feasibility and Preliminary Results of a Robotic Treatment in Patients with Hemiparesis. (26th December 2012) - Sale, Patrizio; Lombardi, Valentina; Franceschini, Marco
Abstract : Background . No strongly clinical evidence about the use of hand robot-assisted therapy in stroke patients was demonstrated. This preliminary observer study was aimed at evaluating the efficacy of intensive robot-assisted therapy in hand function recovery, in the early phase after a stroke onset. Methods . Seven acute ischemic stroke patients at their first-ever stroke were enrolled. Treatment was performed using Amadeo robotic system (Tyromotion GmbH Graz, Austria). Each participant received, in addition to inpatients standard rehabilitative treatment, 20 sessions of robotic treatment for 4 consecutive weeks (5 days/week). Each session lasted for 40 minutes. The exercises were carried out as follows: passive modality (5 minutes), passive/plus modality (5 minutes), assisted therapy (10 minutes), and balloon (10 minutes). The following impairment and functional evaluations, Fugl-Meyer Scale (FM), Medical Research Council Scale for Muscle Strength (hand flexor and extensor muscles) (MRC), Motricity Index (MI), and modified Ashworth Scale for wrist and hand muscles (AS), were performed at the beginning (T0), after 10 sessions (T1), and at the end of the treatment (T2). The strength hand flexion and extension performed by Robot were assessed at T0 and T2. The Barthel Index and COMP (performance and satisfaction subscale) were assessed at T0 and T2. Results . Clinical improvements were found in all patients. No dropouts were recorded during the treatment and all subjects fulfilled the protocol. Evidence of a significant improvement was demonstrated by the Friedman test for the MRC (P < 0.0123 ). Evidence of an improvement was demonstrated for AS, FM, and MI. Conclusions . This original rehabilitation treatment could contribute to increase the hand motor recovery in acute stroke patients. The simplicity of the treatment, the lack of side effects, and the first positive results in acute stroke patients support the recommendations to extend the clinical trial of this treatment, in association with physiotherapy and/or occupational therapy.